Application of project-based learning method in Entrepreneurship education (PKWU) subjects of Labschool UPI - Dzakira Syawalia; Amanda Febrilyanti Suryana Putri; Razka Raditya Fahmi; Dimas Saputra (Curricula: Journal of Curriculum Development, 2024)
This study reviews the application of project-based learning methods in PKWU subjects of SMA Labshool UPI. The subject of Entrepreneurship Education (PKWU) has an important role in preparing students for the world of work and entrepreneurship. In this context, the purpose of the study is to identify the potential and effectiveness of project-based learning methods in improving students' understanding and skills in PPKWU subjects at the senior secondary level. This research also aims to design, implement, and evaluate the implementation of project-based learning methods that can integrate theory with practice in the classroom. This study used qualitative research methods using interview instruments to explore student experiences in the application of Project Based Learning Methods in PKWU subjects at SMA Labschool UPI. The results of this study show that the application of project-based methods in learning Crafts and Entrepreneurship subjects has a positive and significant impact on student development. One key aspect that stands out is the increased involvement of students in learning.   Abstrak Penelitian ini mengulas tentang penerapan metode pembelajaran berbasis proyek pada mata pelajaran PKWU SMA Labschool UPI. Mata pelajaran Pendidikan Kewirausahaan (PKWU) memiliki peran penting dalam mempersiapkan siswa untuk dunia kerja dan kewirausahaan. Dalam konteks ini, tujuan dari penelitian adalah untuk mengidentifikasi potensi dan efektivitas metode pembelajaran berbasis proyek dalam meningkatkan pemahaman dan keterampilan siswa dalam mata pelajaran PPKWU di tingkat sekolah menengah atas. Penelitian ini juga bertujuan untuk merancang, menerapkan, dan mengevaluasi pelaksanaan metode pembelajaran berbasis proyek yang dapat mengintegrasikan teori dengan praktik di dalam kelas. Penelitian ini menggunakan metode penelitian kualitatif dengan menggunakan instrumen wawancara untuk mendalami pengalaman siswa dalam penerapan Metode Pembelajaran Berbasis Proyek (Project Based Learning) pada mata pelajaran PKWU di SMA Labschool UPI. Hasil penelitian ini menunjukkan bahwa penerapan metode berbasis proyek dalam pembelajaran mata pelajaran Prakarya dan Kewirausahaan memiliki dampak yang positif dan signifikan terhadap perkembangan siswa. Salah satu aspek kunci yang menonjol adalah peningkatan keterlibatan peserta didik dalam pembelajaran. Kata Kunci: Kewirausahaan; metode pembelajaran; project based learning